Statement of Argentine pediatric endocrinologists on growth hormone interchangeability - Alonso, Guillermo (2019)
Growth hormone (GH), just like vaccines, antibodies, and other hormones, is a biological medicinal product (BMP); therefore, it is produced by a complex mechanism that is specific to each (trademark) product. BMPs are subjected to prolonged, comprehensive assessment processes and must be approved prior to their use. The patents of early recombinant human GHs are starting to expire, and this has encouraged pharmaceutical companies to manufacture GH in accordance with the processes corresponding to the original products, thus resulting in biosimilar recombinant GH. In Argentina, there are seven different GH trademarks; only one is a biosimilar product: Omnitrope® (Sandoz) is biosimilar to Genotropin® (Pfizer). Other products available in the market include HHT® (Biosidus), Hutrope® (Elly Lilly), NorditropinFlexpro® (Novo Nordisk), Saizen® (Merck), and Zomacton® (Ferring). For an adequate understanding of this article, it is important to outline the characteristics of the different BMPs.1-5